Politeness Strategies on Language Use in Asjitba Village : A Pragmatic Analysis - Ohorella, Hayat Marwan; Susim, Sarah Novita (JOLIES : Journal of Linguistic and English Studies, 2025)
The aim of this research is to explore the politeness strategies used by people of Asjidba Village, Sorong Regency. The recent study was carried under descriptive qualitative method, using pragmatic analysis of Brown and Levinson's Politeness theory. The data collection techniques used are observation, documentation, recording and transcription. The data analysis techniques used are data reduction, data display, and verification. The researcher summed up that Asjitba used three types of politeness strategies, namely: (1) Positive Politeness Strategy, (2) Negative Politeness Strategy, and (3) positive politeness strategy. Among the three strategies, Positive politeness strategy is a language strategy that they used most.